MANAGEMENT OF PRODUCTIVE WAQF IN ACHMAD WARDI EYE HOSPITAL OF BWI-DD IN SERANG BANTEN - Rio Erismen Armen; Nabillah Fauziah Kuswendah; Asmuliadi Lubis (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
The study aims to portray the model of waqf management by Achmad Wardi Eye Hospital (Rumah Sakit Mata Achmad Wardi or RSMAW) established by Indonesian Waqf Board (Badan Wakaf Indonesia or BWI) and Dompet Dhuafa (DD) in Serang, Banten, (hereinafter referred to RSMAW BWI-DD). Generally, the utilization of waqf assets for public facilities in Indonesia is still insignificant. Thus, the large potential of waqf has not yet delivered a significant economic and social impact. The study uses a qualitative method with library study and interviews as the data collection techniques. The findings show that RSMAW BWI-DD has applied all management procedures such planning, organizing, directing, and supervising activities. Meanwhile, the model of waqf management employed by RSMAW BWI-DD focuses on collecting waqf funds with Cash Waqf Linked Sukuk (CWLS) scheme and investing them to Indonesian sovereign sukuk. This model involves several parties, namely waqf nāẓir institution (Lembaga Nazhir Wakaf), Islamic financial institutions (called as Lembaga Keuangan Syariah Penerima Wakaf Uang or LKS PWU, Indonesian Waqf Board (Badan Wakaf Indonesia) and the Indonesian Ministry of Finance. The study concludes that management processes implemented by RSMAW BWI-DD are well-mannered in generating a positive impact to health sector in Indonesia.